UPAYA PENINGKATAN HASIL BELAJAR DAN AKTIVITAS PESERTA DIDIK MELALUI MODEL DISCOVERY LEARNING PADA PEMBELAJARAN TEMATIK KELAS IV SD NEGERI 1 WAY LAGA - Hikmatunnisa, Meilinda (Jurnal Analisis Pendidikan Sosial, 2024)
This research is motivated by the low learning outcomes and activities of students in thematic learning for class IV B SD Negeri 1 Way Laga. The purpose of this study is to improve learning outcomes and student activities through the Discovery Learning model in thematic learning. This type of research is Classroom Action Research (CAR) which is carried out in 3 cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The results showed that the application of the Discovery Learning model could improve student learning outcomes and activities in thematic learning for class IV B SD Negeri 1 Way Laga. This is evident in the first cycle of student learning outcomes obtained by 37.14%, and student activity obtained by 56.25%, and increased in the second cycle the learning outcomes of participants obtained by 57.14% and student activity obtained by 68.75 %. Then it increased again in the third cycle of student learning outcomes obtained by 82.86% and student activity obtained by 85.42%.